Modelling and validation of a novel continuously variable transmission system using slider crank mechanism. (2018) - Rahman, Muhammad Luqman Hakim Abd; Hudha, Khisbullah; Kadir, Zulkiffli Abd; Amer, Noor Hafizah; Aparow, Vimal Rau
Vehicle transmission system transfers torque and speed from the power source to drive wheels. Continuously variable transmission (CVT) system offers smooth ratio transition where it improves acceleration performance and reduces fuel consumption. Currently, most of the CVT system is actuated by the internal hydraulic circuit where compressibility of oil introduces non-linearity to the system causing difficulty in controlling CVT response. Therefore, a new free-hydraulic CVT system is developed to overcome the shortcomings in existing CVT. The proposed CVT system is designed based on belt-driven type which consists of two sets of variable pulley. Each set of variable pulleys is actuated by an electric motor using slider crank mechanism. The mathematical modelling of CVT mechanism is developed by using Lagrange formulation. The results from this study show that the simulation model of CVT mechanism can produce good performance behaviour in following desired radius position of the real CVT mechanism.